Analisis Kemampuan Berpikir Kritis Siswa Terhadap Mata Pelajaran IPAS di SDN 060857 Medan Tembung - Adinda Mutiarahma Siregar; Lala Jelita Ananda (Concept: Journal of Social Humanities and Education, 2024)
This research was carried out with the aim of describing the critical thinking skills of class IV students in science and technology subjects on energy and its changes. This research is descriptive qualitative research. This research was carried out at SDN 060857 Medan Tembung. The subjects of this research were 18 fourth grade students and after that 3 subjects were selected based on the results of the critical thinking ability test which had low, medium and high scores. The instruments used are critical thinking ability tests and interview guidelines. Data collection was carried out by means of ability tests and interviews. To check the validity of the data using triangulation techniques. Data analysis techniques are carried out by reducing data, presenting data and drawing conclusions. The results of this research show the ability to think critically in science subjects in class IV SDN 060857 Medan Tembung on the subject of energy and its changes resulting in an average of 67.77 which is categorized as good, this can be seen from students who meet the critical thinking indicators, namely: Identifying problems, providing arguments, drawing conclusions, and evaluating.